Malignant transformation of endometriosis: pearls and pitfalls at magnetic resonance imaging - Ye. A. Yukhno; I. A. Trofimenko; G. Ye. Trufanov (ABV-press, 2014)
The article analyzes magnetic resonance images of the 117 patients with endometrioid ovarian cysts including 12 patients with ovarian cancer raised from endometrioid cysts. Such symptoms as vascularized solid component formation, cyst enlargement and T2-shading regression showed strong correlation with malignant transformation of endometrioid cyst. The solid component within the cyst needs to be differentiated between malignant tumor growth, decidualization and inflammatory tissue. Magnetic resonance imaging is a powerful non-invasive method of malignant transformation of the endometrioid ovarian cysts.